2017
DOI: 10.1021/jacs.7b02411
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic Reprogramming of the Ligand Specificity of Growth Factor Receptors by Bispecific DNA Aptamers

Abstract: The reprogramming of receptor-ligand interactions affords an opportunity to direct cells to respond to user-defined external cues. Although this has often been achieved via the genetic engineering of receptors, an alternative, nongenetic approach is highly demanded. In this article, we propose the design of oligonucleotide-based synthetic switches that feature the ability to reprogram the ligand specificity of the growth factor receptor. We demonstrated that our synthetic switches induced growth factor signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 33 publications
0
74
0
Order By: Relevance
“…Fore xample,t he Sando group developed an ongenetic approach to reprogram the ligand specificity of RTKs (Figure 4). [45] RTKs are cell surface receptors that regulate fundamental cellular activities,s uch as cell proliferation, migration, and differentiation. [46] Reprograming the ligand specificity of RTKs provided an opportunity to customize cellular signaling and direct cell behavior with external stimuli in au ser-defined manner.U sing ab i-specific DNA aptamer that consisted of an aptamer sequence for binding to the RTK, and another aptamer sequence for binding to the external cue (Platelet-derived growth factor, PDGF), it was found that RTKdimerization and activation could be induced by adding the external cue (PDGF).…”
Section: Dna Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Fore xample,t he Sando group developed an ongenetic approach to reprogram the ligand specificity of RTKs (Figure 4). [45] RTKs are cell surface receptors that regulate fundamental cellular activities,s uch as cell proliferation, migration, and differentiation. [46] Reprograming the ligand specificity of RTKs provided an opportunity to customize cellular signaling and direct cell behavior with external stimuli in au ser-defined manner.U sing ab i-specific DNA aptamer that consisted of an aptamer sequence for binding to the RTK, and another aptamer sequence for binding to the external cue (Platelet-derived growth factor, PDGF), it was found that RTKdimerization and activation could be induced by adding the external cue (PDGF).…”
Section: Dna Nanostructuresmentioning
confidence: 99%
“…[46] Reprograming the ligand specificity of RTKs provided an opportunity to customize cellular signaling and direct cell behavior with external stimuli in au ser-defined manner.U sing ab i-specific DNA aptamer that consisted of an aptamer sequence for binding to the RTK, and another aptamer sequence for binding to the external cue (Platelet-derived growth factor, PDGF), it was found that RTKdimerization and activation could be induced by adding the external cue (PDGF). [45] This concept could be further integrated with existing DNA-based logic circuits or protein-based molecular devices to develop smart and safe regenerative medicines that can induce cell activity upon the application of auser-defined external cue. [45] Figure 2.…”
Section: Dna Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mimicking natural ligand‐trigger receptor activation, RTKs could be engineered with designed DNA nanodevices to reprogram cells to respond to noncognate ligands with artificially promoted cell migration. The Sando group designed a DNA aptamer‐mediated reprogramming of the interaction partner of receptor tyrosine kinases (DRIPaR) strategy to “rewire” RTK‐mediated signaling (Figure B) . The proof‐of‐concept DRIPaR consisted of bispecific aptamers both of the c‐Met aptamer and of another aptamer that bound to different external bio‐macromolecular targets (e.g., PDGF and thrombin).…”
Section: Applicationsmentioning
confidence: 99%
“…The Sando group de-signedaD NA aptamer-mediated reprogramming of the interaction partner of receptor tyrosine kinases (DRIPaR) strategy to "rewire" RTK-mediateds ignaling ( Figure 4B). [62] The proof-ofconcept DRIPaRc onsisted of bispecific aptamers both of the c-Met aptamer and of another aptamer that bound to different externalb io-macromolecular targets (e.g.,P DGFa nd thrombin). c-Met signaling and cell migration were therefore promoted by user-defined signals through the formationo ft ernary complexes between two bispecific aptamersa nd their ligands.…”
Section: Regulation Of Cell Migrationmentioning
confidence: 99%